Stellate ganglion block for posttraumatic pain syndrome - Vatansever, M.; Onal, S.A.; Kuyurtar, F. (My University, 1994)
Whether the severe pain in the course of illness or the treatment difficulties encourage the physicians to apply stellate ganglion block in posttraumatic pain syndrome. 4 patients diagnosed as posttraumatic pain syndrome have had stellate ganglion block 2 times a week totally 6 times. Injection done with 1% 10 ml lidocaine solution given to the stellate region and no analgesic agent given additionally. We relieved the pain which was the most complaining symptom. No complication was seen. There was high analgesic potency comparing with the other methods in the control groups. Because of controlling the pain permitted the patients to exercise this study accepted as a clinic rule in this disease. The orthopaedic and pain units in our hospital decided to be in correlation about this subject.
Keywords: Posttraumatic pain syndrome; Stellate ganglion block